Building public satisfaction with marketing communication strategy and service quality - Susanti, Christina Esti; Srimulyani, Veronika Agustini; Hermanto, Yustinus Budi; Waloyo, Laurensius Anang Setiyo (Manajemen Komunikasi, 2023)
Marketing starts from communicating information related to products and services to the right consumers. Marketing communication is a combination of two studies, namely communication, and marketing. Excellent service quality (ESQ) is an important relationship marketing activity influencing customer satisfaction. In the public sector, there are increasing public demands on the quality of services provided, especially in urban areas that are very easily accessible with the development of information technology and the increasing level of public education. This study aims to provide insight into the importance of marketing communication strategies and ESQ in the public sector to public satisfaction by taking the object of research of the Department of Communication and Information Technology (IT) of Madiun City. The study used a quantitative approach and questionnaires as a data collection tool. The research sample of 304 people represented three sub-districts included in the Madiun City area. The data analysis techniques used are simple linear regression & multiple linear regression analysis. The test results of this study show that the dimensions of ESQ consisting of tangible, reliability, responsiveness, assurance, & empathy, both simultaneously and partially have a positive and significant impact on the satisfaction of the community who use the services of the Department of Communication & IT in Madiun City. The results of this study show the importance of marketing communication strategies and assessment of excellent service quality as an effort by the public sector to increase public satisfaction. Marketing communication strategies can also support government efforts in building regional branding.